Love and the Distance: The Role of Presence in Online Learning - Brown, Keith; Zhang, Zian (Canadian Journal of Education / Revue canadienne de l'éducation, 2024)
The COVID-19 pandemic necessitated a shift to online teaching and learning, prompting concerns about maintaining teacher and student presence in virtual classrooms. Holistic education, emphasizing love, care, and interconnectedness, faces challenges in the digital realm. Holistic educators explore online behaviours, environments, and tools fostering deep presence. Four post-secondary educators were interviewed, revealing a focus on managing emotions for a positive online atmosphere. They utilize positive mental states and contemplative rituals to compensate for the lack of physical presence. Instead of redefining presence, educators use online tools to uphold traditional notions, such as requiring visible cameras. Further research is needed to understand how holistic educators’ exposure to online technologies may impact contemplative ideas of presence.